Analisis Teori Sibernetik Pada Era Pembelajaran 5.0 Dalam Perkembangan Hasil Belajar Siswa Di Kelas VII MTsN 1 Langkat - Riza Wahyuna, Usmaidar, Rani Febriyanni (Ability: Journal of Education and Social Analysis, 2023)
The application of cybernetic learning theory to class VII students of MTsN I Langkat has generally been implemented in Madrasahs where every learning is always related to the internet or computers and smartphones which are used as student learning resources. The learning process that is carried out always utilizes existing artificial intelligence in order to obtain information related to learning so that students are able to process the information obtained into knowledge. The application of cybernetic learning theory has been carried out using various media and methods that utilize information and communication technology that has been integrated with people's lives in the 5.0 era so that students get complete information and are able to process this information into knowledge. The form of learning in the 5.0 era that is carried out in Madrasas is more concerned with process. The information system is processed because the information will determine the learning process that is carried out. The development of student learning outcomes with the application of cybernetic learning theory in the 5.0 learning era in class VII students of MTs Negeri I Langkat has been able to improve student learning outcomes because understanding of the subject matter is better with the cybernetic theory. Era 5.0 learning is very helpful for learning that is carried out because of the extensive support of information technology in providing information to students. In general, the value of student learning outcomes is good and meets the established criteria of completeness.